Heavy menstrual bleeding on direct factor Xa inhibitors: Rationale and design of the MEDEA study. Issue 1 (18th December 2020) - Hamulyák, Eva N.; Wiegers, Hanke M. G.; Scheres, Luuk J. J.; Hutten, Barbara A.; de Lange, Maria E.; Timmermans, Anne; Westerweel, Peter E.; Nijziel, Marten R.; Kruip, Marieke J. H. A.; ten Wolde, Marije; Ypma, Paula F.; Klok, Frederikus A.; et al.
Abstract: Background: In premenopausal women, treatment with direct oral factor Xa inhibitors is associated with an increased risk of heavy menstrual bleeding (HMB) compared with vitamin K antagonists (VKA). Treatment with the direct oral thrombin inhibitor dabigatran appears to be associated with a reduced risk of HMB compared with VKA. These findings come from small observational studies or post hoc analyses of trials in which HMB was not a primary outcome. Use of tranexamic acid during the menstrual period may be effective in patients with HMB, but prospective data regarding efficacy and safety in patients on anticoagulant treatment are lacking. Rationale and Design: A direct comparison of a factor Xa inhibitor and a thrombin inhibitor with HMB as primary outcome, as well as an evaluation of the effects of adding tranexamic acid in women with anticoagulant‐associated HMB is highly relevant for clinical practice. The MEDEA study is a randomized, open‐label, pragmatic clinical trial to evaluate management strategies in premenopausal women with HMB associated with factor Xa inhibitor therapy. Outcomes: Women using factor Xa inhibitors with proven HMB, as assessed by a pictorial blood loss assessment chart (PBAC) score of >150, will be randomized to one of three study arms: (i) switch to dabigatran; (ii) continue factor Xa inhibitor with addition of tranexamic acid during the menstrual period; or (iii) continue factor Xa inhibitor without intervention. The primary outcome is the difference in PBAC score before and after randomization. Here, we present the rationale and highlight several unique features in the design of the study.